UPDATING THE STUDENTS’ MASTERY ON DISCOURSE MARKERS TO IMPROVE THEIR READING SKILLS - Endang Yuliani Rahayu; Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2019)
The current study aimed at justifying that updating or upgrading the mastery on discourse markers (DMs) could improve the students’ reading skills. It is arguably true that DMs do facilitate readers to comprehend texts in terms of the logical and grammatical relation. Therefore, an action research involving 21 students randomly selected as the subjects of the study were conducted in Reading Classes. Pre-test, Post-test 1 and Post-test 2 were administered to generate the data consisting of the progress of their reading skills. Theoretical insights on DMs (function and uses) were also highlighted including the teaching procedures to support the findings of the classroom action research. It turns out that despite the fact that there are 4 types of DMs, only three of them were mostly used in the reading texts, namely contrastive, elaborative and inferential markers. Updating or upgrading DMs proves effective to improve the students’ reading skills as there were increases in scores to indicate improvements. Key words: discourse markers, action research, reading skills